Aprendizagem docente do professor orientador no estágio curricular supervisionado em cursos de licenciatura - Pereira, Sybelle Regina Carvalho (2017)
This thesis is part of the research line of Training, Knowledge and Professional Development of the Post-Graduation Program in Education of the Federal University of Santa Maria and presents as a research theme the learning of the instructor-teacher in supervised curricular training in undergraduate courses Community institution of higher education. It proposes as a general objective: to understand how teacher teaching takes place in the context of supervised curricular internship in undergraduate courses. It aims, therefore, to know the senses produced in the formative, personal and professional trajectory of the guiding teacher; to recognize the senses produced in the dynamics of the pedagogical work and to identify the movements of the teaching learning. The qualitative conception of research delineates the theoretical-methodological design of this study, which was developed in the approach of the sociocultural narrative. The narratives of 14 guiding teachers, co-workers, constituted the elements of the analysis. The collaborating subjects act in 13 undergraduate courses of a community institution of higher education. Documentary analysis and semi-structured narrative interview were used as research instruments. The studies of Vygotski (1993a, 1993b, 1994, 1995); Bakhtin (2010, 2011, 2012a, 2012b); Freitas (2007, 2013); Bolzan (2001, 2006a, 2006b, 2009a, 2016); Ludy and Andre (2013), Bogdan e Biklen (1994), Connelly and Clandinin (1995), form the theoretical subsidies that underlie the methodology of this research. Vygotski (1993a, 1993b, 1994, 1995); Bakhtin (2010, 2011, 2012a, 2012b); Leontiev (1978, 1984, 2014); Bolzan (2001, 2006a, 2006b, 2007, 2009a, 2009b, 2016); Bolzan and Isaia (2010); Isaia (2006); Isaia and Bolzan (2007a, 2007b, 2009a, 2009b, 2009c); Alarcão (2013); Nóvoa (2000); Tardif (2011); Tardif e Lessard (2013); Huberman (2000); Vaillant and Marcelo (2012); Marcelo (1999); Zabalza (2004, 2014); Pimenta (2004); Lima (2012); Daniels (2011); Wertsch (1993); Amorim (2004, 2009); Brait (2005, 2014); Sobral (2010a, 2010b) e Ponzio (2012a, 2012b) help in the understanding of the warp of teaching learning when discussing learning and development, activity and learning, surplus vision, alterity, dialogue, formative processes and trajectory, teaching pedagogical work, pedagogical knowledge . In the interpretation of the narratives, the existence of a central category is explained: teacher learning, which is constituted by two dimensions: the formative trajectory and the pedagogical work. These dimensions are structured by category elements, which are configured by the meanings denoted to these two dimensions. Such structure is dynamized by the teacher learning movements: alterity, dialogue and shared pedagogical knowledge. The study of these aspects allows to defend that the set of senses woven by the teacher learning movements reveals theoretical and methodological aspects that allow the development of strategies which produce both the organization of training processes and the mobilization of the research activity as a way reflect on the Pedagogical practice itself, to produce knowledge, but, fundamentally, to qualify university teaching.